Giambattista Marinos Wort-Zucht-Peitschen und die Gegenreformation in Wien um 1655 Textedition und Kommentar - Noe, Alfred (2015)
Critical edition of the german translation of G. B. Marino's La sferza invettiva, commentary and context of the Counterreformation in Vienna 1655